Impact of Telemonitoring With Exacerbation Prediction Algorithm Versus Telemonitoring Alone on Hospitalizations and Health-Related Quality of Life in Patients With COPD. - Kronborg, Thomas; Hangaard, Stine; Laursen, Sisse Heiden; Hæsum, Lisa Korsbakke Emtekær; Egmose, Julie; Bender, Clara; Secher, Pernille Heyckendorff; Hejlesen, Ole; Udsen, Flemming Witt (Respiratory Care, 2025)
Background: Unreported and untreated exacerbations of COPD have significant negative impacts on health status, disease progression, rate of hospitalization, and readmission. The present study investigated whether a COPD exacerbation prediction algorithm embedded into a telemonitoring system can reduce the number of hospitalizations and improve health-related quality of life (HRQOL) compared with telemonitoring alone. Methods: A total of 137 participants were enrolled in this single-blinded randomized controlled trial. Patients were eligible for inclusion if they had a COPD diagnosis, were adults, had fixed residence in Aalborg Municipality in Denmark, and already used an existing telemonitoring system. The primary outcome was the between-group difference in the number of acute hospitalizations per subject after 6 months of follow-up. Secondary outcomes included the difference in all-cause hospitalization, HRQOL measured by 12-item Short Form Health Survey (version 2) and EuroQol-5 Dimension Questionnaire (EQ-5D-5L), and mortality after 6 months. Data were analyzed according to the intention-to-treat principle. Results: The adjusted incidence rate ratio (IRR) of acute hospitalizations per subject was 1.30 (95% CI 0.50–3.38). The odds ratio (OR) for the hospitalization proportion was 2.10 (95% CI: 0.72–6.09). The adjusted IRR for the number of all-cause hospitalizations were 1.25 (95% CI: 0.51–3.07), whereas the OR for an all-cause hospitalization proportion was 1.92 (95% CI: 0.70–5.26). The adjusted OR for mortality was 0.46 (95% CI: 0.11–1.94). The adjusted mean difference in the physical component score and mental component score was 0.77 (95% CI: −1.72 to 3.47) and 0.91 (95% CI: −2.63 to 4.72), respectively, and −0.05 (95% CI: −0.14 to 0.03) for the EQ-5D index score. All results were nonstatistically significant. Conclusions: No definitive conclusions could be drawn regarding the effect on hospitalizations and HRQOL when implementing a COPD prediction algorithm in addition to telemonitoring.